First record of the genus Paragigagnathus Amitai and Grinberg, 1971 (Mesostigmata: Phytoseiidae) from Saudi Arabia with description of a new species. Issue 11 (26th March 2016) - Alatawi, Fahad J.; Kamran, M.; Basahih, J.
Abstract: The genus Paragigagnathus Amitai and Grinberg (Acari: Phytoseiidae) is reported for the first time from Saudi Arabia. Paragigagnathus desertorum (Amitai and Swirski) and P. insuetus (Livshitz and Kuznetsov) were collected from Acacia sp. (Fabaceae) and Tamarix sp. (Tamaricaceae), respectively. Paragigagnathus madinaensis n. sp. is described and illustrated. The new species was found on Tamarix sp. in association with Obdulia daadi Al-Gboory (Prostigmata: Tenuipalpidae) from Al-Riyadh and Al-Madina regions of Saudi Arabia.